Relationship between Emotional Intelligence and Job Competency at Petaling Jaya Police Headquarters, Selangor, Malaysia - Kanesan, Pavitra (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study investigates the relationship between emotional intelligence and job competency in junior and senior police officers using correlational research design. About 296 junior and 109 senior police officers from Petaling Jaya District Police Headquarters, Selangor participated. Self-administered instruments were used to collect data. Data analysed by using Statistical Package for the Social Sciences (SPSS) version 20. Pearson Correlation Coefficient Analysis, Independent-samples T-test, and one-way between-groups analysis of variance (ANOVA) were carried out to test the hypotheses developed for this particular study. The findings revealed that junior police officers’ nature of emotional intelligence was contributed largely by self-emotional appraisal and regulation of emotion. Meanwhile, senior police officers’ nature of emotional intelligence was contributed mainly by use of emotion. Both junior and senior police officers demonstrated lower others’ emotional appraisal. Next, findings showed that junior police officers’ nature of job competency was contributed largely by interpersonal skills and least by communication skills. Meanwhile, senior police officers’ nature of job competency was highly contributed by interpersonal skills and leadership. However, senior police officers demonstrated less problem-solving skills. It was found that emotional intelligence and job competency are strongly correlated. Both junior and senior police officers who demonstrated high emotional intelligence also demonstrated high job competency. The findings showed a significant difference in emotional intelligence between junior and senior police officers. Senior police officers’ emotional intelligence is higher compared to junior police officers’. Findings also showed a significant difference in job competency between junior and senior police officers. Senior police officers demonstrated higher job competency compared to junior police officers. No significant differences in emotional intelligence by demographic factors of age and length of service were observed in both junior and senior police officers. The findings suggested that competency-based training using adaptive emotional intelligence skills might enhance junior and senior police officers’ job performance.